Effect of seismic bed rock acceleration ratio on the material, flexural and shear behavior of a building in ethiopia based on ES EN 1998–1:2015. (2021) - Jebasingh Daniel, J.
Abstract: A salubrious structural modeling and construction of a building absolutely relies on the endowment of the designer with profound expertise concerning the seismic impacts and cost-effective fabrication of the structure. The seismic impact like earthquake prone regions are more likely to be focused in favor of detailing an efficient construction planning, which is analyzed in detail in this paper by considering a shopping complex building with Ethiopian code as a study. This analysis is performed using the Finite element software tool which facilitates the designer to envisage the material consumption based on the seismic impacts across the six seismic zones in the county and the efficacy is validated by manual computations which satisfies the Ethiopian code standards. The performance criteria is endorsed by considering the factors like bending and shear impact patterns, base shear/seismic weight of the building and the requisite of concrete and steel materials for the six seismic zones.